2023
DOI: 10.38035/jmpd.v1i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Internet of Things: Analisis Efektivitas Kerja, Perilaku Individu dan Supply Chain

Abstract: The Internet of Things is developing in many sectors, especially in the industrial and household sectors. Internet of Things is expected to be a new solution in carrying out daily activities, especially those that are closely related to objects or machines. The concept of the Internet of Things itself is developing smart technology into an object, with the goal of innovation that makes activities more effective and efficient. Examples of the application of the Internet of Things in the industrial and household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
2
10
0
5
Order By: Relevance
“…Thus, it can be concluded that according to researchers, the description of the data on the guidance provided by caregivers to students at the Aisyiyah Koto Tangah Padang Orphanage looks Less Good (Nofrialdi, Saputra, & Saputra, 2023).…”
Section: Results and Discussion 1 Coaching Overview A Overview Of Gui...mentioning
confidence: 99%
“…Thus, it can be concluded that according to researchers, the description of the data on the guidance provided by caregivers to students at the Aisyiyah Koto Tangah Padang Orphanage looks Less Good (Nofrialdi, Saputra, & Saputra, 2023).…”
Section: Results and Discussion 1 Coaching Overview A Overview Of Gui...mentioning
confidence: 99%
“…Istilah Internet of Things dibentuk oleh dua kata yaitu Internet dan Things [1]. Internet merupakan suatu sistem jaringan komputer yang secara global saling terhubung dengan menggunakan standar Internet Protocol Suite (TCP/IP) guna mewadahi miliaran pengguna di seluruh dunia [2]. Internet of Things menggambarkan dunia di mana apa saja dapat terhubung dan berkomunikasi dengan cara yang cerdas yang pernah ada sebelumnya [2].…”
Section: Pendahuluanunclassified
“…Proses pembelajaran merupakan proses yang dimana terdapat beberapa kegiatan interaksi antara siswa dengan guru dan terjadi komunikasi timbal balik yang berlangsung dalam situasi edukatif dalam mencapai tujuan belajar (Nofrialdi, Saputra, & Saputra, 2023). Proses pembelajaran merupakan proses interaksi antara peserta didik atau siswa pada kegiatan pembelajaran berlangsung (Mahaputra & Saputra, 2021).…”
Section: Proses Pembelajaranunclassified